Antiviral efficacy of nanoparticulate vacuolar ATPase inhibitors against influenza virus infection - Hu CMJ (Dove Medical Press, 2018)
Che-Ming Jack Hu,1,2,* You-Ting Chen,3,* Zih-Syun Fang,1,3 Wei-Shan Chang,3 Hui-Wen Chen2,3 1Institute of Biomedical Sciences, Academia Sinica, Taipei, Taiwan; 2Research Center for Nanotechnology and Infectious Diseases, Taipei, Taiwan; 3Department of Veterinary Medicine, National Taiwan University, Taipei, Taiwan *These authors contributed equally to this work Background: Influenza virus infections are a major public health concern worldwide. Conventional treatments against the disease are designed to target viral proteins. However, the emergence of viral variants carrying drug-resistant mutations can outpace the development of pathogen-targeting antivirals. Diphyllin and bafilomycin are potent vacuolar ATPase (V-ATPase) inhibitors previously shown to have broad-spectrum antiviral activity. However, their poor water solubility and potential off-target effect limit their clinical application. Methods: In this study, we report that nanoparticle encapsulation of diphyllin and bafilomycin improves the drugs’ anti-influenza applicability. Results: Using PEG-PLGA diblock copolymers, sub-200 nm diphyllin and bafilomycin nanoparticles were prepared, with encapsulation efficiency of 42% and 100%, respectively. The drug-loaded nanoparticles have sustained drug release kinetics beyond 72 hours and facilitate intracellular drug delivery to two different influenza virus-permissive cell lines. As compared to free drugs, the nanoparticulate V-ATPase inhibitors exhibited lower cytotoxicity and greater in vitro antiviral activity, improving the therapeutic index of diphyllin and bafilomycin by approximately 3 and 5-fold, respectively. In a mouse model of sublethal influenza challenge, treatment with diphyllin nanoparticles resulted in reduced body weight loss and viral titer in the lungs. In addition, following a lethal influenza viral challenge, diphyllin nanoparticle treatment conferred a survival advantage of 33%. Conclusions: These results demonstrate the potential of the nanoparticulate V-ATPase inhibitors for host-targeted treatment against influenza. Keywords: influenza virus, vacuolar ATPase inhibitor, diphyllin, bafilomycin, nanoparticles